2020
DOI: 10.1111/faf.12489
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of Atlantic bluefin tuna

Abstract: The reproductive success of fish populations depends on their reproductive potential and offspring survival to maturity. The reproductive potential affects recruitment and hence populations' resilience and productivity. Extensive research carried out throughout the current century has improved our understanding of the reproductive biology of the Atlantic bluefin tuna (ABFT), Thunnus thynnus. Yet, crucial questions still remain unresolved. This paper examines key factors that drive ABFT reproductive performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…However, it is widely reported that the Atlantic cod may not spawn annually once reaching maturation (Rideout et al., 2000 and references therein cited). Electronic tagging experiments and fishery data have shown that not all the adult individuals of the highly migratory species Atlantic bluefin tuna visit any of the known spawning grounds during the spawning season, thus leading to the disputed hypothesis that only a fraction of the adult population contributes to recruitment (Bello et al., 2021 ; Corriero et al., 2020 ; Medina, 2020 ), a reproductive strategy that could involve follicular atresia as mechanism underlying spawning omission.…”
Section: Ecological Aspects and Impact Of Atresia On Fish Reproductive Potentialmentioning
confidence: 99%
“…However, it is widely reported that the Atlantic cod may not spawn annually once reaching maturation (Rideout et al., 2000 and references therein cited). Electronic tagging experiments and fishery data have shown that not all the adult individuals of the highly migratory species Atlantic bluefin tuna visit any of the known spawning grounds during the spawning season, thus leading to the disputed hypothesis that only a fraction of the adult population contributes to recruitment (Bello et al., 2021 ; Corriero et al., 2020 ; Medina, 2020 ), a reproductive strategy that could involve follicular atresia as mechanism underlying spawning omission.…”
Section: Ecological Aspects and Impact Of Atresia On Fish Reproductive Potentialmentioning
confidence: 99%
“…The occurrence of early atretic stages of yolked follicles (α and β atresia) is often used in fish maturity classifications and characterization of temporal reproductive patterns (e.g., Lowerre-Barbieri et al, 2011;Schaefer, 1998Schaefer, , 2001. Degenerated yolked follicles are helpful to distinguish reproductively inactive, but mature, individuals from young fish that have not yet attained maturity, which is a crucial issue in fisheries science (Arrizabalaga et al, 2019;Medina, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of appropriate biometric models holds notable importance in the case of ABFT, as its age-at-reproduction is presently a matter of debate [ 19 , 20 ]. The International Commission for the Conservation of Atlantic Tunas (ICCAT) manages ABFT on the assumption that the two recognized stocks, i.e., the Western and the Eastern Atlantic stocks, have different sexual maturation schedules and strict spawning fidelity to the respective reproductive areas (Gulf of Mexico and the Mediterranean Sea) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The International Commission for the Conservation of Atlantic Tunas (ICCAT) manages ABFT on the assumption that the two recognized stocks, i.e., the Western and the Eastern Atlantic stocks, have different sexual maturation schedules and strict spawning fidelity to the respective reproductive areas (Gulf of Mexico and the Mediterranean Sea) [ 21 ]. This disputed assumption is backed by controversial determinations of main life traits, such as age- and size-at-sexual maturity [ 19 , 20 ]. In this respect, any piece of evidence able to shed light on the age- and size-at-first reproduction is highly welcome.…”
Section: Introductionmentioning
confidence: 99%